MODERNIZATION OF THE TRADING AND LOGISTIC SYSTEM OF THE FRUIT AND VEGETABLE SECTOR OF CHUBUT PROVINCE, PATAGONIA - Jatib, María Inés; Repetto, Horacio A.; Bentivegna, Marina; Assusa, Maria Sol (European Scientific Journal, ESJ, 2015)
The Valle Inferior del Río Chubut (VIRCH) is the main valley irrigated of Patagonia –Argentina- with 23,000 hectares (69,000 acres) where, after livestock, the vegetable and fruit production has gained second place in importance because of its localization underneath the Barrier of Animal and Plant Health of Rio Colorado, which makes the products safer since it is used much less agrochemicals, and consequently offers higher quality and less perishable, although the valley production do not cover local consumption. Because of that, the Provincial Government with the National Government’s technical support created a Program denominated "Development and Strengthening of an Agrifood Platform for fruit and vegetable in Chubut Province", counting with local and international financing. This proposal tries to ensure the provision or supply of fruits and vegetables to local consumers for which requires infrastructure and adequate tools to improve transparency of commercial transactions. In the meantime, to transforming the system of wholesale marketing it is required the construction of a platform as a place of development of new services companies and improvement the current ones. This Unit will be a right marketplace for buying wholesale horticultural products coming from other markets outside the region and for stimulates consumption through the implementation of food safety and quality control among other advantages such as fair prices. The main purpose is to analyze modernization of the Trading System and Logistics for fruits and vegetables of the province of Chubut.